Analysis of Flood Risk Areas by Weighting the Analytic Network Process (ANP) Method - Suciana, Ajeng Titin; Suhartanto, Ery; Wahyuni, Sri (Fakultas Teknik, Universitas Brawijaya, 2024)
Flooding is one of the disasters that often occurs in the Karangmumus Sub Watershed, causing more than 400 housing units to be flooded in 2021. In this study using the Weighted Scoring method, the parameters are soil type, slope, land cover, rainfall, and land use. They determine the weight of each flood parameter using the Analytic Network Process (ANP) method. ANP is a decision-making method that takes into account the relationships and dependencies. This research study aims to identify flood-risk areas that produce flood-risk maps. The ANP analysis results show that the land use parameter weighs 50% of the total weight. The risk class is divided into four parts: not risk, somewhat risk, risk, and very risk. The largest flood-risk area is the “very riskous” class, with an area of 29,288 km2. The suitability of the analysis results with BNPB data is 80%, thus indicating that the suitability is very high. The map of the analysis results with the map from BNPB shows an NSE value of 0.764 and an R-value of 0.956, identifying the plot and the relationship between the two data as very strong. The research results are expected to be a parameter for effective and efficient policy-making in flood disaster management. Map-making uses a Geographic Information System (GIS) with an intersect tool.